The Effect of HDI, Open Unemployment Rate, and Poverty on Income Disparity in Riau Islands Province in 2011-2022 - Wilna Br Hutabarat; Sudarsana Arka (Universitas Nusantara PGRI Kediri, 2023)
Income disparity needs to be addressed so that the level of disparity can be low and controlled so that it can implement development policies properly and improve the welfare of the community. This research aims to analyze the effect of the HDI, Open Unemployment Rate, and Poverty on Income Disparity in Riau Islands Province in 2011-2022. The development of the HDI, Open Unemployment Rate, Poverty and Income Disparity in Riau Islands Province fluctuated considerably during 2011- 2022. This research used panel data from 7 regencies/cities and 1 province from 2011-2022. The results of this research explain that the HDI, Open Unemployment Rate, and Poverty simultaneously have a significant effect on Income Disparity in Riau Islands Province. HDI has a negative and partially significant effect on Income Disparity in Riau Islands Province. Open Unemployment Rate and Poverty have no partial effect on Income Disparity in Riau Islands Province.